Ulcerative colitis – recent and potential methods of treatment - review - Tomasik, Mikołaj; Warzyszak, Paweł; Małek, Róża; Milczek, Maria; Żołyniak, Wojciech; Hawranik, Izabela; Niski, Szymon; Żaba, Ziemowit; Lisowska, Aleksandra; Skrzypek, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Ulcerative colitis (UC, colitis ulcerosa) belongs to a group of inflammatory bowel diseases of unexplained etiology. It is a diffuse nonspecific inflammation of the mucosa of the rectum or rectum and colon, leading to ulceration in more severe cases. Despite a decline in the incidence of ulcerative colitis in developed countries, the prevalence continues to rise due to increasingly predominant benign course of the disease with a low mortality rate. The purpose of this review is to summarize latest directions and discoveries in research of ulcerative colitis. Materials and methods: This review is based on articles published in Pubmed between 2017 and 2022 by searching keywords ulcerative colitis treatment, ulcerative colitis guidelines. State of knowledge: Currently, many independent scientific societies represent a consensus position on the standard management of patients with UC, while recent therapeutic options are constantly emerging due to intensive research. These options require the involvement of multiple medical centers to determine their position in future guidelines. Conclusion: Although ulcerative colitis is a disease that is diagnosed and detected relatively easily, due to its chronic nature, relatively high prevalence in the population and lack of causal treatment options, it is an important direction for further research.